’Where water wells up’ : Revisiting a forgotten deposition tradition from the Late Bronze Age on Funen, Denmark - Beck, Malene Refshauge; Frost, Lise; Enevold, Renée; Marsden, Patrick (Danish Journal of Archaeology, 2023)
The article presents a deposition of ornaments from the Late Nordic Bronze Age period V. An archaeological excavation along with non-pollen Palynomorph (NPP) and pollen ana- lysis has resulted in new knowledge about the poorly illuminated Bronze Age tradition of spring offerings. With a starting point in the find at Hedegyden this article aims to improve the understanding of the Bronze Age depositional practices in relation to springs. The article presents the ornaments, but focuses on their context as regards to the relationship between the objects within the deposition, as well as the site of deposition. Based on the strati- graphic observations, the preserved organic materials in the Hedegyden find and the scientific analyses, a chaîne opératoire is presented for the various sub-elements and phases of the depositional act.